Retrospective Study of Mammary Lesions in Bitches - Uberlândia, MG, Brazil - Andrade, Mariana Batista; Guimarães, Ednaldo Carvalho; Coleto, Arlinda Flores; Soares, Nicolle Pereira; Medeiros-Ronchi, Alessandra Aparecida (Acta Scientiae Veterinariae, 2017)
Background: Mammary tumors are a type of neoplasia that are most commonly found in female dogs and are mostly malignant. The aim of this study, performed in the Laboratory of Veterinary Pathology of the Federal University of Uberlândia (LVP-FUU) from 2004 to 2014, was to determine the prevalence of mammary tumors in bitches and to verify the relationship between the epidemiological factors (age and breed) and clinicopathological aspects (ulceration, tumor size, and malignancy) in the occurrence of tumors. Materials, Methods & Results: A retrospective study was carried out using histopathological information retrieved from the LPV-UFU database. We collected the information on age and breed of female dogs, as well as about the location, macroscopic aspects, and histological diagnosis of mammary lesions. Only female dogs were considered for this study; a total of 911 histopathological protocols (with only one diagnosis) were analyzed along with 36 protocols that presented more than one diagnosis of mammary tumor. The age of animals ranged from one to 20 years, and the mean age was 9.99 years. The most affected breeds of dogs were: Cross breed (39.56% - 288/728) and Poodle (20.19% - 147/728). The inguinal glands were most affected by the malignant tumors (P < 0.05). A prevalence of tumors bigger than 5 cm in diameter (T3) was observed in the elderly animals (P = 0.0154) and in the inguinal mammary glands (P = 0.044). Simple carcinoma was the most frequent histological type. Discussion: Research shows that more than 40% of the tumors in bitches are located in the mammary glands, emphasizing the importance of this type of neoplasia in female dogs. Mammary tumors develop more frequently in the middle-aged and elderly bitches, with the highest occurrence being in the age range of 8 and 10 years, corroborating our observation in the present study that the mean age of bitches was 9.99 years. In this survey, a higher incidence was observed in mongrel bitches compared to that in the Poodle breed. Some authors affirm that there is no racial predisposition for the occurrence of this pathology; however, a compilation of data suggests a predisposition of at least 10 breeds, with the involvement of an as yet unidentified genetic component. Of these, six breeds (Poodle, Cocker Spaniel, Pointer, Maltese, Yorkshire Terrier, and Dachshund) were found to be predisposed to mammary tumors in this study. The percentage (49.23%) of malignant tumors found in the inguinal glands is consistent with the findings reported in literature, and might be associated with a greater amount of parenchyma, abundance of hormone receptors in these glands, and vascularization provided by the caudal superficial epigastric artery and vulvar branches of external pudendal artery. Tumor size is considered to be a prognostic factor and tumors ≤ 3 cm in diameter (T1) have a better prognosis. Consequently, the prevalence of tumors ≥ 5 cm in diameter (T3) in elderly animals is probably related to malignancy of the lesions, because tumors usually progress to a worse histological grade with time. The higher occurrence of T3 in inguinal glands might be related to the abundance of parenchyma and/or hormonal receptors in them. As in the present study, data from literature refer to the superiority of malignant histological types, with prevalence varying between 68 and 91%. When prolonged, the time between the onset of tumor and clinical evaluation may be a determinant in the progression from benign to malignant tumors. Among the malignant neoplasms, simple carcinoma was observed to be prevalent, followed by mixed tumors with carcinoma, in agreement with the results of several studies. It is concluded that mammary tumors are more prevalent in older mongrel dogs and Poodle. Attention should be paid to inguinal mammary tumors, because these are mainly malignant.